Answer:
Above the x-axis
Explanation:
Lets assume a polygon that has coordinates at A(3,2), B(3,4),C(6,4),D(6,2).
This polygon is in the 1st quadrant
so rotate it clockwise 90° about the origin, you apply the rule that point of object (h,k) will change to (k,-h) hence
A (3,2) ⇒A'(2,-3)
B (3,4) ⇒ B'(4,-3)
C (6,4) ⇒C' (4,-6)
D (6,2) ⇒D' (2,-6)
the image is in the 4th quadrant
Reflecting the rotated figure on the x-axis we get
A''=(2,3)
B''=(4,3)
C''=(4,6)
D''=(2,6)
it is on the 1st quadrant
The translation is(-3,3)
The image will be
A'''=(-3+2,3+3) = (-1,6)
B'''=(-3+4,3+3)= (1,6)
C'''=(-3+4,6+3)= (1,9)
D'''=(-3+2,6+3)= (-1,9)
the final figure above x-axis